2011
DOI: 10.1007/s10811-011-9679-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular weight on the antioxidant property of low molecular weight alginate from Laminaria japonica

Abstract: In this study, three alginate fractions with different molecular weights and ratios of mannuronic acid (M) to guluronic acid (G) were prepared by enzymatic hydrolysis and ultrafiltration to assess the antioxidant property of alginates from Laminaria japonica with molecular weight below 10 kDa. The antioxidant properties of different molecular weight alginates were evaluated by determining the scavenging abilities on superoxide, hydroxyl, and hypochlorous acid and inhibitory effect on Fe 2 + -induced lipid pero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…While the IC 50 of the other fractions (GLP and DAP) cannot be determined within the test dosage range (1–4 mg/L), which indicates that DAP and GLP have lower effect than SCP and ULLP on the removal of hydroxyl radicals, this may be due to GLP and DAP molecular weights being higher than that of SCP and ULLP. This result further supports the hypothesis that low molecular weight may function as effective antioxidants, and this is in agreement with results of Zhao et al and Zhang et al who demonstrated that the antioxidant activities have a certain relationship with molecular weight [43,44]. …”
Section: Discussionsupporting
confidence: 92%
“…While the IC 50 of the other fractions (GLP and DAP) cannot be determined within the test dosage range (1–4 mg/L), which indicates that DAP and GLP have lower effect than SCP and ULLP on the removal of hydroxyl radicals, this may be due to GLP and DAP molecular weights being higher than that of SCP and ULLP. This result further supports the hypothesis that low molecular weight may function as effective antioxidants, and this is in agreement with results of Zhao et al and Zhang et al who demonstrated that the antioxidant activities have a certain relationship with molecular weight [43,44]. …”
Section: Discussionsupporting
confidence: 92%
“…Sato and others () reported that the thermal stability of carp myofibrillar proteins was improved by conjugation to alginate oligosaccharide, which suggests that this protein modification improved the functional properties of fish myofibrillar proteins. In addition, Zhao and others () reported that this oligosaccharide could prevent lipid oxidation and scavenge hydroxyl (OH) and superoxide (O 2 − ) radicals. Furthermore, oligosaccharides prepared from alginate could be combined easily with ionic cross‐linking agents such as Ca 2+ and Mg 2+ in muscle proteins (Lee and others ) to form a stable 3‐dimensional network with a high water content.…”
Section: Resultsmentioning
confidence: 99%
“…AOS used as a dietary supplement has also been reported to beneficially affect the growth of weaned pigs, most likely by improving intestinal morphology and barrier function. In the same application, AOS inhibited mitochondria-dependent apoptosis of enterocytes [52]. In research related to human ageing, guluronic acid restored the expression of the superoxide dismutase 2, glutathione peroxidase 1, catalase, glutathione S-transferase, iNOS, and myeloperoxidase genes to normal levels, indicating that it might reduce the age-related changes [169].…”
Section: Other Activitiesmentioning
confidence: 94%
“…AOS (enzymatic degradation) with a molecular weight of less than 1 kDa are better scavengers of superoxide, hydroxyl, and hypochlorous acid free radicals than alginate with a molecular weight of 1-10 kDa, ascorbic acid, and carnosine. In addition, the AOS with molecular weight of 1-6 kDa have higher antioxidant activity against superoxide and hypochlorous acid free radicals than AOS with molecular weight of 6-10 kDa, even if they have a similar M/G ratio [52]. Thus, low molecular weight AOS exert higher antioxidant activity.…”
Section: Antioxidant Activitymentioning
confidence: 95%